Floral and phytosociological diversity of selected lawns in the city of Szczecin - Renata Gamrat; Edyta Saran (Acta Scientiarum Polonorum. Formatio Circumiectus, 2018)
Species composition of lawns in the housing estates, planted – among other reasons – in order to diversify the urban landscape, is often modified and enriched with other, spontaneously appearing species. The aim of the present work was to determine the floristic and phytosociological diversity of selected housing estate lawns of three different age groups, in the city of Szczecin, in three neighbouring housing estates (Niebuszewo, Warszewo, and Żelechowa). It was assumed that over the years, lawns are gradually becoming weaker, which may be due to the occurrence of negative anthropogenic factors of increasing intensity. It was found that despite the one designated plant community in all the analysed housing estate lawns (namely, Poa pratensis – Festuca rubra), there are differences between the studied areas, in terms of the number of species occurring therein, and the values of selected ecological (environmental) indicators.